PENGAWASAN SYARIAH, TATA KELOLA, DAN KINERJA BANK SYARIAH - OKTALINA EKASARI; DENY DWI HARTOMO (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2019)
This research focused on examining the effects of the board the syariah supervisor, the board of directors, the independent board of commissioners and internal ceo power on performance, and the board structure on performance. The results showed that: 1) There is a significant relationship between the syariah supervisory board and the performance, 2) There is a significant relationship between the board of directors and the performance, 3) There is a significant relationship between independent board and performance, 4) There is no significant relationship between Internal CEO and performance, 5) There is a significant relationship between board structure and performance. Keywords: Sharia Supervision, Governance, Performance, Bank Syariah